2022
DOI: 10.1186/s12951-022-01729-7
|View full text |Cite
|
Sign up to set email alerts
|

Repellent active ingredients encapsulated in polymeric nanoparticles: potential alternative formulations to control arboviruses

Abstract: Dengue, yellow fever, Chinkungunya, Zika virus, and West Nile fever have infected millions and killed a considerable number of humans since their emergence. These arboviruses are transmitted by mosquito bites and topical chemical repellents are the most commonly used method to protect against vector arthropod species. This study aimed to develop a new generation of repellent formulations to promote improved arboviruses transmission control. A repellent system based on polycaprolactone (PCL)-polymeric nanoparti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 67 publications
1
1
0
Order By: Relevance
“…The authors observed remarkably higher drug release for IR3535 from the nanoparticles than from the nanocomposite gel, whereas slight differences were observed when assessing geraniol from the nanoparticles and the nanocomposite gels. However, similar profiles were observed in the permeation study [ 55 ]. Bini et al prepared nanocomposite formulations in which nanoparticles were embedded in gelatin gels.…”
Section: Resultssupporting
confidence: 85%
“…The authors observed remarkably higher drug release for IR3535 from the nanoparticles than from the nanocomposite gel, whereas slight differences were observed when assessing geraniol from the nanoparticles and the nanocomposite gels. However, similar profiles were observed in the permeation study [ 55 ]. Bini et al prepared nanocomposite formulations in which nanoparticles were embedded in gelatin gels.…”
Section: Resultssupporting
confidence: 85%
“…Additionally, nanotechnology can be applied to other strategies to fight malaria, such as better drug delivery in malaria cases, as reviewed by our group [ 12 ], and the nanoformulation of repellents to control disease transmission [ 85 ].…”
Section: Plants and Nano Formulationsmentioning
confidence: 99%